PENGARUH PROTOKOL KESEHATAN, HARGA DAN FASILITAS TERHADAP KEPUTUSAN BERKUNJUNG DI DESTINASI WISATA PADA PANDEMI COVID-19 - Fahimah, Mar’atul; Umsa, Ani Yufida (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2022)
The COVID-19 pandemic has had a major impact on tourist destinations. The number of tourist visits decreased after this outbreak spread. Government regulations oblige to comply with health protocols and avoid crowds. The COVID-19 pandemic has been going on for more than a year. This study aims to examine whether the variables of health protocols, prices and facilities affect the decision to visit. This study uses a quantitative approach, which means its use to describe or explain a phenomenon using quantitative data. The technique used in this sample research uses non-probability, precisely using purposive sampling taken from visitors who came during the time span of the Covid-19 pandemic. The results of this study indicate that the Health Protocol does not affect the decision to visit tourist destinations. Price Variables affect Visiting Decisions, price supporting factors include pricing, payment methods and price discounts. Facilities influence the decision to visit, the supporting factors for facilities include completeness, condition and comfort. The Facility variable has the biggest influence on the decision to visit a tourist destination during the Covid-19 pandemic.